Emulsified fiber asphalt anti-collapse plugging agent and preparation method thereof

By mixing basalt fiber powder and MMH positive electroplastic glue with emulsified asphalt to form an emulsified fiber asphalt anti-collapse sealing agent, the problem of the poor effect of existing emulsified asphalt anti-collapse agent in high-temperature deep wells is solved, and stronger prevention is achieved Collapse effect and stability.

CN119432334AActive Publication Date: 2025-02-14PETROCHINA CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202310974943.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

The existing emulsified asphalt anti-collapse sealing agent is not effective in high-temperature deep wells, and the adhesion, sealing layer strength and stability after modification have not yet achieved ideal results.

Method used

By mixing basalt fiber powder and MMH positive electroplastic glue with emulsified asphalt, an emulsified fiber asphalt anti-collapse sealant is formed, which improves its density, viscosity and static suspension performance, and enhances adhesion to the formation and strength of the sealing layer.

Benefits of technology

The anti-collapse sealing effect of emulsified fiber asphalt anti-collapse sealing agent is significantly improved, the strength and adhesion of the asphalt sealing layer are enhanced, and the system stability and cost are low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432334A_ABST
    Figure CN119432334A_ABST
Patent Text Reader

Abstract

The invention provides an emulsified fiber asphalt anti-collapse plugging agent and a preparation method thereof. The emulsified fiber asphalt anti-collapse plugging agent is formed by mixing emulsified asphalt, MMH positive electricity gel and basalt fiber powder. The basalt fiber powder is distributed in the emulsified asphalt anti-collapse plugging agent in a three-dimensional disordered manner, so that the strength of an asphalt plugging layer can be enhanced, the monofilament diameter of the basalt fiber powder is consistent with the average crack distribution of most shale stratums, the basalt fiber powder has better compatibility, the adhesive force between the plugging layer and the stratums after demulsification of the emulsified asphalt is enhanced, and the anti-collapse plugging effect is improved. The MMH positive electricity adhesive improves the stability of the whole system due to the characteristics of the MMH positive electricity adhesive, and is beneficial to adsorption, demulsification and sheet connection of emulsified asphalt and a stratum with negative charges. The emulsified fiber asphalt anti-sloughing plugging agent enhances the strength of a plugging layer after demulsification of emulsified asphalt and the adhesive force between the plugging layer and the stratum, and improves the anti-sloughing plugging effect. In addition, the preparation process is easy to operate, the cost is low, and the anti-collapse plugging agent has extremely high application prospects in the field of anti-collapse plugging of well walls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a preparation method and application of an emulsified fiber asphalt anti-collapse plugging agent. Background Art

[0002] Emulsified asphalt is a commonly used wellbore stabilizer used in the field of oil and gas drilling. The main principle is that emulsified asphalt will demulsify after being adsorbed into the formation. The demulsified asphalt is connected to each other, softened and deformed under the action of the formation temperature, and squeezed into the cracks and pores of the formation under the action of the pressure difference, plugging the cracks and pores of the wellbore wall to achieve the anti-collapse plugging effect. However, the anti-collapse plugging effect of emulsified asphalt is greatly affected by the adhesion between asphalt and the formation, the strength of the asphalt plugging layer, and the softening point of asphalt: the adhesion between asphalt and the formation is mainly through the adsorption of asphalt and the formation to paste on the surface of mud shale, and this adhesion sometimes does not reach the level expected by drilling engineers; the strength of the asphalt plugging layer is related to the thickness of the plugging layer and the performance of the asphalt itself, and it is also one of the main properties that drilling engineers hope to improve; the raw asphalt of asphalt treatment agents is petroleum asphalt and natural asphalt, and the softening point is mostly in the range of 40-100℃. For deep high-temperature formations, especially complex formations above 150℃, it is difficult to effectively plug the micro-cracks in the formation. It is for the above reasons that drilling engineers have been working hard in these three aspects to improve the effectiveness of emulsified asphalt anti-collapse plugging agents.

[0003] At present, in order to improve the adhesion of emulsified asphalt to the formation, the strength of the asphalt plugging layer, and the softening point of asphalt, the relevant technical methods modify the emulsified asphalt to obtain an emulsified asphalt anti-collapse agent with an improved softening point, which can be used in deep wells with higher temperatures. However, the adhesion of the asphalt to the formation and the strength of the asphalt plugging layer after demulsification need to be further improved to meet the needs of higher anti-collapse plugging performance. Although the technology proposed in existing research to improve the adhesion of emulsified asphalt to the formation and the strength of the asphalt plugging layer has been promoted, there are problems such as insufficient compatibility of the modified emulsified asphalt with the formation, lack of stability of the system, and high cost, and the adhesion of the emulsified asphalt to the formation and the strength of the asphalt plugging layer still do not achieve the ideal effect. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides an emulsified fiber asphalt anti-collapse plugging agent and a preparation method thereof, wherein the emulsified asphalt is modified by basalt fiber powder and MMH positive gel (i.e., Mixed metal hydroxide, hereinafter referred to as MMH positive gel) to obtain an emulsified fiber asphalt anti-collapse plugging agent with greatly improved anti-collapse plugging effect. The specific content of the invention is as follows:

[0005] In a first aspect, the present invention provides an emulsified fiber asphalt anti-collapse plugging agent, wherein the emulsified fiber asphalt anti-collapse plugging agent is mixed with emulsified asphalt, MMH positive electrode glue and basalt fiber powder:

[0006] Wherein, the mass percentage of the emulsified asphalt is 97.5-98.5%;

[0007] The mass percentage of the basalt fiber powder is 1 to 1.5%;

[0008] The mass percentage of the MMH positive glue is 0.5-1%.

[0009] In a second aspect, the present invention provides a method for preparing the emulsified fiber asphalt anti-collapse plugging agent described in the first aspect, the preparation method comprising the following steps:

[0010] S1, heating the emulsified asphalt, and then adding the basalt fiber powder to the emulsified asphalt to obtain a mixture of basalt and emulsified asphalt;

[0011] S2, heating the mixture, adding MMH positive electrode gel to the mixture, and obtaining the emulsified fiber asphalt anti-collapse plugging agent.

[0012] Optionally, in step S1, the emulsified asphalt is anionic emulsified asphalt.

[0013] Optionally, in step S1, the mass ratio of the basalt fiber powder to the emulsified asphalt is (1-1.5%): (97.5-98.5%).

[0014] Optionally, in step S1, the monofilament diameter of the basalt fiber powder is 5 to 8 microns;

[0015] The length of the basalt fiber powder is 10 to 60 microns.

[0016] Optionally, in step S1, the aspect ratio of the basalt fiber powder is (2:1) to (8:1).

[0017] Optionally, in step S1, the density of the basalt fiber powder is 1.75 g / cm 3 .

[0018] Optionally, in step S1, the heating temperature is 60°C.

[0019] Optionally, in step S2, the mass ratio of the MMH positive gel and the mixture is (0.5-1%): (99-99.5%).

[0020] Optionally, in step S2, the heating temperature is 60°C.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The present invention provides an emulsified fiber asphalt anti-collapse plugging agent, which is mixed with emulsified asphalt, MMH positive gel and basalt fiber powder. The experimental results show that the density of the emulsified fiber asphalt anti-collapse plugging agent provided in the embodiment of the present application has increased, the apparent viscosity AV has increased from 8.5mPa.s to 48mPa.s, the growth rate is as high as 464%, the dynamic shear force YP has increased from 4.5Pa to 24Pa, the growth rate is 433%, and the static shear force has increased from 1 / 2Pa / Pa to 16 / 32Pa / Pa, which shows that the emulsified fiber asphalt anti-collapse plugging agent has extremely strong dynamic and static suspension performance. After observing in a large number of cylinders for 24 hours, the emulsified fiber asphalt anti-collapse plugging agent has no stratification, and no basalt fiber powder sinking phenomenon is observed, indicating that the system of the anti-collapse plugging agent has good stability. And the expansion rate of the bentonite adsorbed by the emulsified fiber asphalt anti-collapse plugging agent is as low as 11.6%, which has improved adsorption. The emulsified fiber asphalt anti-collapse plugging agent obtained by modifying the emulsified asphalt with basalt fiber powder and MMH positive gel has good stability and compatibility with the formation, thereby enhancing the strength of the plugging layer and the adhesion to the formation after the emulsified asphalt is demulsified, and improving the anti-collapse plugging effect. In addition, the entire preparation process is simple to operate and low in cost, and has a very high application prospect in the field of anti-collapse plugging of well walls.

[0023] The present invention provides a method for preparing an emulsified fiber asphalt anti-collapse plugging agent, which comprises adding basalt fiber powder to emulsified asphalt and mixing evenly, and further adding MMH positively charged gel and mixing evenly to obtain an emulsified fiber asphalt anti-collapse plugging agent. Among them, the basalt fiber powder in the emulsified asphalt anti-collapse plugging agent can greatly enhance the strength of the asphalt plugging layer after the emulsified asphalt is demulsified, and enhance the compatibility of the asphalt plugging layer with the formation after the emulsified asphalt is demulsified, thereby enhancing the adhesion between the plugging layer and the formation, and significantly improving the anti-collapse plugging effect of the emulsified asphalt. The MMH positively charged gel is added to the emulsified asphalt due to its own characteristics, which improves the stability of the system and is very beneficial to the storage, transportation and use of the prepared emulsified fiber asphalt anti-collapse plugging agent; an appropriate excess of MMH positively charged gel makes the emulsified fiber asphalt anti-collapse plugging agent present positive characteristics, which is beneficial to the adsorption, demulsification and connection of the emulsified asphalt with the negatively charged formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1A flow chart of a method for preparing an emulsified fiber asphalt anti-collapse plugging agent provided in an embodiment of the present invention is shown;

[0026] Figure 2 A schematic diagram showing the performance enhancement principle of the emulsified fiber asphalt anti-collapse plugging agent provided in an embodiment of the present invention is shown. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.

[0028] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0029] Technologies, methods, and apparatus known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, such technologies, methods, and apparatus should be considered part of the authorization specification.

[0030] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. If not otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0031] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] The emulsified asphalt anti-collapse agent provided by the author of this application in the patent "An emulsified asphalt anti-collapse agent and its preparation method, ZL201810117538.9" generates a reaction product with a three-dimensional network structure by the reaction of epoxy resin and curing agent, and then dissolves the emulsified asphalt in the three-dimensional network structure. Since the three-dimensional network structure has strong stability, the temperature resistance of the prepared emulsified asphalt anti-collapse agent can be improved, thereby improving the softening point of the asphalt after the emulsified asphalt is demulsified, so that it can be used in deep wells with higher temperatures. The softening point of asphalt can be increased from 60°C to above 150°C, thereby meeting the needs of high-temperature deep well anti-collapse; but in the application process in recent years, it was found that the adhesion between the asphalt and the formation and the strength of the asphalt sealing layer after the emulsified asphalt is demulsified need to be further improved to meet the needs of higher anti-collapse and sealing performance.

[0033] Yang Yuliang, Li Yueming, Ma Shichang and others reported in the article "Research and Application of Asphalt in Oil Drilling" in the first issue of Volume 6 of "Xinjiang Petroleum and Natural Gas" that different types of products will be obtained by using different processes and different raw materials for asphalt modification. The main methods adopted are: direct feeding, solvent method, blending method, sulfonation method, emulsification method, graft copolymerization method, etc., and the performance of the products obtained is also different; in terms of improving the adhesion between asphalt and the formation, adding relevant materials such as lime powder and sulfonated lignite powder to emulsified asphalt can improve the adhesion between asphalt and the formation, but years of application have shown that the effect of adding lime powder and sulfonated lignite powder to emulsified asphalt on improving the adhesion between asphalt and the formation still cannot reach the level expected by on-site engineers.

[0034] In the process of emulsified asphalt modification, economic efficiency and system stability are important considerations. In the published patent (application number 201410730046.9) "A nanocarbon fiber modified emulsified asphalt and its preparation method", an emulsified asphalt for road repair construction is provided, which is modified by adding nanocarbon fibers. The nanocarbon fibers worth millions of yuan per ton will greatly increase the unit price of emulsified asphalt products. The drilling anti-collapse plugging agent market cannot accept products with too high a unit price. In addition, in order to maintain a density of 1.85g / cm 3 The suspension stability of nano-carbon fiber in the system, the patent adds polyvinyl alcohol, sodium carboxymethyl cellulose, polyacrylamide and other viscosity-enhancing stabilizers, the addition amount is 0.5% mass volume ratio, because the density of emulsified asphalt is 0.98~~1.05g / cm 3 , with a density of 1.85g / cm 3 The difference between nano-carbon fibers is large. The amount of viscosity-enhancing stabilizer added can only maintain the stability of the system for a short period of time. After a long time, the nano-carbon fibers will settle and cannot be used. To maintain the stability of the system for a long time, the amount of viscosity-enhancing stabilizer must be greatly increased, which will cause the emulsified asphalt to lose fluidity and will also be unusable.

[0035] In the process of emulsified asphalt modification, compatibility with the formation is also an important consideration. In the published patent (application number 202010963483.0) "A composite fiber emulsified asphalt mixture and its preparation method", an emulsified asphalt for road repair construction modification is provided. The fiber used is one of polyester fiber, polypropylene fiber and carbon fiber. Their diameters reach 150 to 300 microns, while the microcracks in the formation are usually distributed between nanometers and tens of microns. Fibers with too large diameters cannot be effectively inserted into the microcracks in the formation.

[0036] Based on the poor stability of the above-mentioned emulsified asphalt anti-collapse agent, poor compatibility with the formation and high cost, when used for the well wall, the strength of the asphalt plugging layer after the emulsified asphalt is demulsified and the adhesion between the plugging layer and the formation still cannot achieve the desired effect. The present invention proposes to modify the emulsified asphalt with MMH positive gel and basalt fiber powder to obtain an emulsified fiber asphalt anti-collapse plugging agent. Among them, the basalt fiber powder is distributed in a three-dimensional disorder in the emulsified asphalt anti-collapse plugging agent. As the emulsified asphalt is demulsified and connected in the formation, the basalt fiber powder forms a mesh power layer in the asphalt, which can greatly enhance the strength of the asphalt plugging layer. The monofilament diameter of the basalt fiber powder is 5 to 8 microns, which is consistent with the average crack distribution of most shale formations, and has good compatibility. And the basalt fiber powder is 10 to 60 microns in length, which can be inserted into the formation cracks, greatly enhancing the adhesion effect of the asphalt plugging layer and the formation after the emulsified asphalt is demulsified. Therefore, basalt fiber powder can greatly enhance the strength of the asphalt plugging layer after the emulsified asphalt is demulsified in the emulsified asphalt anti-collapse plugging agent, and enhance the compatibility of the asphalt plugging layer with the formation after the emulsified asphalt is demulsified, thereby enhancing the adhesion between the plugging layer and the formation, and significantly improving the anti-collapse plugging effect of the emulsified asphalt. The MMH positively charged gel is added to the emulsified asphalt due to its own characteristics, which improves the stability of the system and is very beneficial to the storage, transportation and use of the prepared emulsified fiber asphalt anti-collapse plugging agent; an appropriate excess of MMH positively charged gel makes the emulsified fiber asphalt anti-collapse plugging agent present positive characteristics, which is beneficial to the adsorption, demulsification and connection of the emulsified asphalt with the negatively charged formation.

[0037] The emulsified fiber asphalt anti-collapse plugging agent obtained by the present invention has good stability and compatibility with the formation, and the emulsified fiber asphalt anti-collapse plugging agent also greatly enhances the strength of the asphalt plugging layer after the emulsified asphalt is demulsified and the adhesion between the plugging layer and the formation, thereby improving the anti-collapse plugging effect. In addition, the entire preparation process is simple to operate and low in cost, and has extremely high application prospects in the field of anti-collapse plugging of well walls. The specific implementation methods are as follows:

[0038] In a first aspect, the present invention provides an emulsified fiber asphalt anti-collapse plugging agent, wherein the emulsified fiber asphalt anti-collapse plugging agent is formed by mixing emulsified asphalt, MMH positive electrode glue and basalt fiber powder.

[0039] The present invention provides an emulsified fiber asphalt anti-collapse plugging agent, in which basalt fiber powder is distributed in a three-dimensional disordered manner in the emulsified asphalt anti-collapse plugging agent. As the emulsified asphalt breaks and connects in the formation, the basalt fiber powder forms a mesh strength layer in the asphalt, which can greatly enhance the strength of the asphalt plugging layer. In addition, the monofilament diameter of the basalt fiber powder is 5 to 8 microns, which is consistent with the average crack distribution of most shale formations, that is, the compatibility of the emulsified asphalt with the formation is improved. In addition, the basalt fiber powder is 10 to 60 microns in length, and is inserted into the formation cracks, which greatly enhances the adhesion between the asphalt plugging layer and the formation after the emulsified asphalt breaks, and improves the anti-collapse plugging effect. MMH positively charged gel is a kind of aluminum magnesium hydroxide, which is mainly composed of divalent metal ions and trivalent metal ions and has a hydrotalcite-like layered structure hydroxide with permanent positive charge. It has a special rheological property when combined with anionic emulsified asphalt: it is in a pseudo-solid state when static and has a certain elasticity. It produces extremely strong shear thinning performance when stirred, that is, "solid-liquid duality". The reason is mainly caused by the formed MMH-water-anionic emulsified asphalt complex structure. When static, all the water in the system is polarized to form a grid structure, so the structural strength is large, which is manifested as a high static shear force τ0. However, this polarized water chain is easily destroyed, so it is easy to dilute when stirred. At the same time, the destruction and formation of the polarized water chain structure are very rapid, and the conversion from pseudo-solid to fluid or vice versa can be completed in a very short time. This property is very beneficial to the storage, transportation and use of emulsified fiber asphalt anti-collapse plugging agent; an appropriate excess of MMH positively charged gel makes the emulsified fiber asphalt anti-collapse plugging agent present positive characteristics, which is beneficial to the adsorption, demulsification and connection of emulsified asphalt with negatively charged formations.

[0040] The invention provides an emulsified fiber asphalt anti-collapse plugging agent, wherein the mass percentage of the emulsified asphalt is 97.5-98.5%, the mass percentage of the basalt fiber powder is 1-1.5%, and the mass percentage of the MMH positive electrode glue is 0.5-1%.

[0041] In a second aspect, the present invention provides a method for preparing the emulsified fiber asphalt anti-collapse plugging agent described in the first aspect. Figure 1 The flowchart of the method for preparing the emulsified fiber asphalt anti-collapse plugging agent provided in the embodiment of the present invention is shown as follows: Figure 1 As shown, the preparation method comprises the following steps:

[0042] S1, heating the emulsified asphalt, and then adding the basalt fiber powder to the emulsified asphalt to obtain a mixture of basalt and emulsified asphalt;

[0043] When this step is implemented, first turn on the colloid mill, set the temperature at 60°C, and circulate the heating of the anionic emulsified asphalt until the temperature reaches 60°C. According to the mass ratio of basalt fiber powder 1-1.5% and emulsified fiber asphalt anti-collapse plugging agent 98.5-99%, basalt fiber powder is slowly added to the emulsified asphalt according to 2-3 cycles to ensure that the basalt fiber powder is evenly dispersed in the emulsified asphalt.

[0044] S2, heating the mixture, adding MMH positive electrode gel to the mixture, and obtaining the emulsified fiber asphalt anti-collapse plugging agent.

[0045] When this step is implemented, the colloid mill is turned on, the temperature is set at 60°C, and the mixture of basalt fiber powder and emulsified asphalt is heated in a cycle until the temperature reaches 60°C. According to the mass ratio of 0.5-1% of MMH positive gel and 99-99.5% of the mixture of emulsified asphalt and basalt fiber powder, after two or three cycles, the MMH positive gel is added to the emulsified asphalt. Ensure that the MMH positive gel is evenly dispersed in the emulsified asphalt.

[0046] Figure 2 The schematic diagram of the performance enhancement of the emulsified fiber asphalt anti-collapse plugging agent provided by the embodiment of the present invention is shown as follows: Figure 2 As shown in the figure, in the emulsified asphalt, the basalt fibers are distributed in a three-dimensional disordered manner. After the emulsified asphalt is adsorbed on the well wall and demulsified, the basalt fiber powder forms a network strength layer in the asphalt, which greatly enhances the strength of the asphalt plugging layer. The single fiber diameter of the basalt fiber powder is 5 to 8 microns, which is consistent with the average crack distribution of most shale formations, so that some basalt fibers can be inserted into the formation cracks. The basalt fiber powder is 10 to 60 microns in length, which makes the asphalt plugging layer and the formation as if countless nails were driven into it, greatly enhancing the adhesion between the plugging layer and the formation after the emulsified asphalt is demulsified.

[0047] In order to enable those skilled in the art to more clearly understand the present invention, the emulsified fiber asphalt anti-collapse plugging agent and its application described in the present invention are now described in detail through the following embodiments and test examples.

[0048] Example 1

[0049] 98.15 parts by mass of anionic emulsified asphalt, 1 part by mass of basalt fiber powder, and 0.85 parts by mass of MMH positive electrode gel.

[0050] Weigh 981.5g of anionic emulsified asphalt, set the temperature of the heated colloid mill at 60°C, and heat the symmetrically taken anionic emulsified asphalt in a cycle until the temperature reaches 60°C. Weigh 10g of basalt fiber powder, and slowly add the basalt fiber powder to the emulsified asphalt for 2 to 3 cycles to ensure that the basalt fiber powder is evenly dispersed in the emulsified asphalt. Weigh 8.5g of MMH positive gel, and slowly add the MMH positive gel to the emulsified asphalt to which the basalt fiber powder has been added for 2 to 3 cycles to ensure that the MMH positive gel is evenly dispersed in the emulsified asphalt to obtain an emulsified fiber asphalt anti-collapse plugging agent.

[0051] Example 2

[0052] 98.5 parts by mass of anionic emulsified asphalt, 1 part by mass of basalt fiber powder, and 0.5 part by mass of MMH positive electrode gel.

[0053] Weigh 985g of anionic emulsified asphalt, set the temperature of the heated colloid mill at 60°C, and heat the symmetrically taken anionic emulsified asphalt in a cycle until the temperature reaches 60°C. Weigh 10g of basalt fiber powder, and slowly add the basalt fiber powder to the emulsified asphalt for 2 to 3 cycles to ensure that the basalt fiber powder is evenly dispersed in the emulsified asphalt. Weigh 5g of MMH positively charged gel, and slowly add the MMH positively charged gel to the emulsified asphalt to which the basalt fiber powder has been added for 2 to 3 cycles to ensure that the MMH positively charged gel is evenly dispersed in the emulsified asphalt to obtain an emulsified fiber asphalt anti-collapse plugging agent.

[0054] Example 3

[0055] 97.5 parts by mass of anionic emulsified asphalt, 1.5 parts by mass of basalt fiber powder, and 1 part by mass of MMH positive electrode gel.

[0056] Weigh 975g of anionic emulsified asphalt, set the temperature of the heated colloid mill at 60°C, and heat the symmetrically taken anionic emulsified asphalt in a cycle until the temperature reaches 60°C. Weigh 15g of basalt fiber powder, and slowly add the basalt fiber powder to the emulsified asphalt for 2 to 3 cycles to ensure that the basalt fiber powder is evenly dispersed in the emulsified asphalt. Weigh 10g of MMH positively charged gel, and slowly add the MMH positively charged gel to the emulsified asphalt to which the basalt fiber powder has been added for 2 to 3 cycles to ensure that the MMH positively charged gel is evenly dispersed in the emulsified asphalt to obtain an emulsified fiber asphalt anti-collapse plugging agent.

[0057] Example 4

[0058] 98 parts by mass of anionic emulsified asphalt, 1 part by mass of basalt fiber powder, and 1 part by mass of MMH positive electrode gel.

[0059] Weigh 980g of anionic emulsified asphalt, set the temperature of the heated colloid mill at 60℃, and heat the symmetrically taken anionic emulsified asphalt in a cycle until the temperature reaches 60℃. Weigh 10g of basalt fiber powder, and slowly add the basalt fiber powder to the emulsified asphalt for 2 to 3 cycles to ensure that the basalt fiber powder is evenly dispersed in the emulsified asphalt. Weigh 10g of MMH positive gel, and slowly add the MMH positive gel to the emulsified asphalt to which the basalt fiber powder has been added for 2 to 3 cycles to ensure that the MMH positive gel is evenly dispersed in the emulsified asphalt to obtain an emulsified fiber asphalt anti-collapse plugging agent.

[0060] Example 5

[0061] 98 parts by mass of anionic emulsified asphalt, 1.5 parts by mass of basalt fiber powder, and 0.5 parts by mass of MMH positive electrode gel.

[0062] Weigh 980g of anionic emulsified asphalt, set the temperature of the heated colloid mill at 60℃, and heat the symmetrically taken anionic emulsified asphalt in a cycle until the temperature reaches 60℃. Weigh 15g of basalt fiber powder, and slowly add the basalt fiber powder to the emulsified asphalt for 2 to 3 cycles to ensure that the basalt fiber powder is evenly dispersed in the emulsified asphalt. Weigh 5g of MMH positive gel, and slowly add the MMH positive gel to the emulsified asphalt with basalt fiber powder added for 2 to 3 cycles to ensure that the MMH positive gel is evenly dispersed in the emulsified asphalt to obtain an emulsified fiber asphalt anti-collapse plugging agent.

[0063] Experimental Example 1

[0064] This experimental example is used to verify the suspension performance observation, testing and anti-collapse plugging performance detection of the emulsified fiber asphalt anti-collapse plugging agent prepared in Example 1, Example 2, Example 3 and Example 4.

[0065] (1) Suspension stability of emulsified fiber asphalt anti-collapse plugging agent

[0066] The suspension performance test results of the emulsified fiber asphalt anti-collapse plugging agent provided in the above Example 1 were compared with those of the emulsified asphalt without basalt fiber powder and MMH positive gel. The results can be seen in Table 1:

[0067] Table 1 Suspension stability of emulsified fiber asphalt anti-collapse plugging agent

[0068]

[0069]

[0070] From the test results, we can see that the density of the emulsified fiber asphalt anti-collapse plugging agent has increased slightly, the apparent viscosity AV has increased from 8.5mPa.s to 48mPa.s, a growth rate of 464%, the dynamic shear force YP has increased from 4.5Pa to 24Pa, a growth rate of 433%, and the static shear force has increased from 1 / 2Pa / Pa to 16 / 32Pa / Pa, indicating that the emulsified fiber asphalt anti-collapse plugging agent has extremely strong dynamic and static suspension properties. After observing in a large number of cylinders for 24 hours, the emulsified fiber asphalt anti-collapse plugging agent showed no stratification and no sinking of basalt fiber powder.

[0071] (2) Anti-collapse and plugging performance of emulsified fiber asphalt anti-collapse plugging agent

[0072] Table 2 Comparison of the performance of emulsified fiber asphalt anti-collapse plugging agent and common anti-collapse agent in inhibiting bentonite expansion

[0073]

[0074] Table 2 is a comparison of the expansion inhibition performance of bentonite by emulsified fiber asphalt anti-collapse plugging agent and commonly used anti-collapse agents. From Table 2, it can be seen that when 4% sulfonated asphalt, 4% FT-3000, and 4% emulsified asphalt are added to the slurry, the expansion of bentonite in the slurry is well inhibited, and the expansion rates are 18.8%, 14.0%, and 14.8%, respectively; after adding 4% emulsified fiber asphalt anti-collapse plugging agent, the expansion rate is 11.6%, which is the best one in controlling expansion performance, indicating that the emulsified fiber asphalt anti-collapse plugging agent is better adsorbed on the bentonite surface and has a better anti-collapse plugging effect.

[0075] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0076] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.

[0077] The above is a detailed introduction to an emulsified fiber asphalt anti-collapse sealing agent and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technical personnel in the field, according to the idea of ​​the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. An emulsified fiber asphalt anti-collapse plugging agent, characterized in that: The emulsified fiber asphalt anti-collapse plugging agent is made by mixing emulsified asphalt, MMH positive electrode glue and basalt fiber powder: Wherein, the mass percentage of the emulsified asphalt is 97.5-98.5%; The mass percentage of the basalt fiber powder is 1 to 1.5%; The mass percentage of the MMH positive glue is 0.5-1%.

2. A method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 1, characterized in that: The preparation method comprises the following steps: S1, heating the emulsified asphalt, and then adding the basalt fiber powder to the emulsified asphalt to obtain a mixture of basalt and emulsified asphalt; S2, heating the mixture, adding MMH positive electrode gel to the mixture, and obtaining the emulsified fiber asphalt anti-collapse plugging agent.

3. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S1, the emulsified asphalt is anionic emulsified asphalt.

4. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S1, the mass ratio of the basalt fiber powder to the emulsified asphalt is (1-1.5%): (97.5-98.5%).

5. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S1, the monofilament diameter of the basalt fiber powder is 5 to 8 microns; The length of the basalt fiber powder is 10 to 60 microns.

6. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S1, the aspect ratio of the basalt fiber powder is (2:1) to (8:1).

7. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S1, the density of the basalt fiber powder is 1.75 g / cm 3 .

8. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S1, the heating temperature is 60°C.

9. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S2, the mass ratio of the MMH positive gel and the mixture is (0.5-1%): (99-99.5%).

10. The method for preparing the emulsified fiber asphalt anti-collapse plugging agent according to claim 2, characterized in that: In step S2, the heating temperature is 60°C.

Citation Information

Patent Citations

  • Emulsified asphalt modified by carbon nanometer fiber and preparing method thereof

    CN105315684A

  • An emulsified asphalt anti-collapse agent and its preparation method

    CN108373909B

  • Composite fiber emulsified asphalt mixture and preparation method thereof

    CN111995338A

  • Nanometer plugging agent for drilling fluid and preparation method thereof

    CN103602323A

  • Aqueous asphalt / wax emulsions for use in gypsum compositions and building products

    CN103842170A